Aggregation dynamics and foraging behaviour of striped red mullet Mullus surmuletus in the western Mediterranean Sea. Issue 5 (26th April 2016) - Ajemian, M. J.; Kenworthy, M. D.; Sánchez‐Lizaso, J. L.; Cebrian, J.
Abstract : Habitat‐related heterogeneity of striped red mullet Mullus surmuletus heterospecific foraging assemblages was examined off the coast of Spain. Video‐based focal‐follows conducted on 122 M. surmuletus assemblages (446 total individuals) revealed an array of attendant species ( n = 7) with composition linked to benthic habitat complexity; bare sandy substrata were characterized by homospecific groups of M. surmuletus, while habitats with rock and vegetation attracted a variety of scrounging labrids and sparids. Although the nature of the relationship between M. surmuletus and attendants requires further exploration, the present study indicates that substratum composition can be a driving factor explaining the dynamics of this heterospecific assemblage.